2011
DOI: 10.4103/0973-1482.80433
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor status and its clinicopathological correlation in post-menopausal breast cancer patients of Kumaon region of Uttarakhand

Abstract: The receptor positivity of steroid receptors was more in higher age groups, but the incidence of receptor positivity was lower than that reported in earlier studies. No statistically significant association was found between receptor status and clinical presentation of breast cancer, histopathological status of tumor and metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Discordant findings in the study may be attributed to the race, as earlier reports were based on western population. [11] The proportion of breast carcinoma with HER2/neu overexpression is very low (2.4%), although not statistically significant, compared to 10 -34% HER2/neu positive breast carcinomas as reported earlier. [19] Thus the more aggressive breast carcinomas as reported do not appear to be due to HER2/neu overexpression.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Discordant findings in the study may be attributed to the race, as earlier reports were based on western population. [11] The proportion of breast carcinoma with HER2/neu overexpression is very low (2.4%), although not statistically significant, compared to 10 -34% HER2/neu positive breast carcinomas as reported earlier. [19] Thus the more aggressive breast carcinomas as reported do not appear to be due to HER2/neu overexpression.…”
Section: Discussionmentioning
confidence: 53%
“…Results in the study of histological grades of tumors and receptor status are in agreement with reports of earlier studies which have shown that poorly differentiated tumors are more common in receptor negative patients. [11] Similarly we found significant correlation between necrosis and HER-2/neu overexpression (P < 0.05).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The average ERpositivity for white women in the US is 77% [8]. Studies done in India and in Indian emigrants have found ERpositivity in Indian women to be 34.5% [14], 35.88% [12], 37.83% [15], 38.6% [11], 49.2% [13], 50.5% [9], and 55.1% [16]. ERpositivity in premenopausal and postmenopausal women was found to be 56.1% and 47.4% respectively.…”
Section: Discussionmentioning
confidence: 99%